2016
DOI: 10.3389/fpls.2016.00243
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Priming with Silicon on the Growth and Tolerance of Maize Plants to Alkaline Stress

Abstract: Silicon (Si) has been known to augment plant defense against biotic and abiotic pressures. Maize (Zea maize L.) is classified as a Si accumulator and is relatively susceptible to alkaline stress. In this study, seeds of maize were grown in pots and exposed to various concentrations of Na2CO3 (0, 25, 50, and 75 mM) with or without 1.5 mM Si in the form of sodium metasilicate Na2O3Si.5H2O for 25 days. Alkaline-stressed plants showed a decrease in growth parameters, leaf relative water content (LRWC), and the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
90
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(100 citation statements)
references
References 52 publications
8
90
2
Order By: Relevance
“…Recently, priming the defense system of the plants has been of particular interest to the scientific community, and our findings therefore confirm reports of the priming-mediated defense responses of the plants to fungal infections [14,70]. For plants, to cope with stress is a complex task, and responses may sometimes overlap [16,71]. The defense measures, however, may be interconnected to understand the plant response to extremely challenging situations such as biotic and abiotic stresses [72,73].…”
Section: Biostimulation Of Defense System Leads To Induced Resistancesupporting
confidence: 85%
“…Recently, priming the defense system of the plants has been of particular interest to the scientific community, and our findings therefore confirm reports of the priming-mediated defense responses of the plants to fungal infections [14,70]. For plants, to cope with stress is a complex task, and responses may sometimes overlap [16,71]. The defense measures, however, may be interconnected to understand the plant response to extremely challenging situations such as biotic and abiotic stresses [72,73].…”
Section: Biostimulation Of Defense System Leads To Induced Resistancesupporting
confidence: 85%
“…In recent years, many experiments revealed that the application of silicon (Si) plays critical roles in plant tolerance to salt stress (Coskun et al 2016;Aras and Eşitken 2018a). Silicon application has been observed to enhance tolerance of many stressors such as drought, and alkaline conditions (Abdel Latef and Tran 2016;Ma et al 2016). Silicon is the second most abundant element on earth and plays an important role in stress tolerance, flowering and fruit quality (Dehghanipoodeh et al 2016;Kim et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Ashraf and Rauf () have reported that under salt stress, priming of maize seeds with CaCl 2 improved the final germination, rate of germination, and fresh and dry biomasses of plumules and radicles compared to untreated control and H 2 O‐primed seeds. Recently, Abdel Latef and Tran () have reported a positive role of Si 2+ seed priming in alleviating the negative effects of alkaline stress on maize growth by improving water status, enhancing photosynthetic pigments, accumulating osmoprotectants rather than proline, activating the antioxidant machinery and maintaining the balance of K + /Na + ratio. Maize seed priming with 1% ZnSO 4 not only enhanced plant growth but also increased the final grain yield and seed Zn 2+ contents in plants grown on soil with limited Zn 2+ availability (Harris et al., ).…”
Section: Introductionmentioning
confidence: 99%